Design And Optimization of Milling Multi Tip Cutter by Varying Depth Parameters - Suresh, S.; Mamidi, Pruthvi Mamidi; Radha, Aloori (International Journal of Psychosocial Rehabilitation, 2025)
Surface accuracy in milling is one of the major aspects while machining the hardened materials. The parameter setting of CNC machining operations often relies on practical experience. In some cases, the parameters are even selected using trial and error that often leads to increased tool costs and the production time. The surface finish will increase with the number of cutting tool tips used in the cutter, related to this depth of cut also leads to the surface finish as well as tool wear. The complexity in special tool design for complex profiles machining with good surface finish will depends on depth of cut, the present work deals with the two form of tools known as multi tip cutter for facing and four flute bull nose cutter. The differentiation in varying depth of cut with constant feed and speed in both the cases will be optimised and the surface finish will be compared. MEKINO 3-axis VMC used for the experimental evaluation with 4-tip cutters and the parameters optimised for better surface finish.